B.V. Chmielevskis and his research into the history of the old mathematics in Lithuania - Banionis, Juozas (Lietuvos matematikos rinkinys, 2005)
B.V. Chmielevskis (1913–1980) after finishing the studies of classical philology and mathematics taught different subjects of mathematics at Vilnius Pedagogical Institute (VPI) from 1959 to 1976 and was distinguished for his research into the  history of the old mathematics.B.V. Chmielevskis's scientific publications form two separate groups. The first one comprises publications on the general history of mathematics and the second one consists of publications on the history of Lithuanian mathematics. The publications on the general history of mathematics are concerned with Archimedes's, F. Viet's, I. Newton's, G. Galileo’s scientific heritage. Publications of the second group are devoted to mathematical education at the old Vilnius University (VU) in 1579–1803. In the latter publications the scientist analyzed interpretations of classical mathematicians' works in the texts of VU professors and students. B.V. Chmielevskis's publications were published in Lithuanian mathematicians' digests and proceedings of VPI.The main theoretical issues concerning researches in the history of mathematics are reflected in B.V. Chmielevskis's doctorate dissertation in physics and mathematics, which was maintained in 1971.
Keywords: history of mathematics; Archimede's textes; mathematics in old Vilnius University